2021
DOI: 10.1101/2021.10.18.464790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiota mediated plasticity promotes thermal adaptation inNematostella vectensis

Abstract: At the current rate of climate change, it is unlikely that multicellular organisms will be able to adapt to changing environmental conditions through genetic recombination and natural selection alo. Thus, it is critical to understand alternative mechanisms that allow organisms to cope with rapid environmental changes. Here, we used the sea anemone Nematostella vectensis as model to investigate the microbiota as putative source of rapid adaptation. Living in estuarine ecosystems, highly variable aquatic environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 132 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Rapidly dividing microbes are predicted to undergo adaptive evolution within weeks to months. Adaptation of the microbiota can occur via changes in absolute abundancies of specific members, acquisition of novel genes, mutation and/or horizontal gene transfer (Baldassarre, Ying, et al, 2021;Bang et al, 2018;Bay & Palumbi, 2015;Edwards, 2020;van Oppen et al, 2018). Here, we provide evidence for genotypespecific microbial plasticity, leading to genotype-specific restructuring of the microbial network in response to environmental stimuli.…”
Section: Microbial Plasticity Is Promoting Animal Adaptationsmentioning
confidence: 74%
See 3 more Smart Citations
“…Rapidly dividing microbes are predicted to undergo adaptive evolution within weeks to months. Adaptation of the microbiota can occur via changes in absolute abundancies of specific members, acquisition of novel genes, mutation and/or horizontal gene transfer (Baldassarre, Ying, et al, 2021;Bang et al, 2018;Bay & Palumbi, 2015;Edwards, 2020;van Oppen et al, 2018). Here, we provide evidence for genotypespecific microbial plasticity, leading to genotype-specific restructuring of the microbial network in response to environmental stimuli.…”
Section: Microbial Plasticity Is Promoting Animal Adaptationsmentioning
confidence: 74%
“…Differences in prokaryotic community composition in different environments have been documented in many other marine invertebrates and are considered to reflect local acclimation (A Hernandez-Agreda et al, 2016;Glasl et al, 2019;Goldsmith et al, 2018;van Oppen et al, 2018). We have recently shown that the restructuring of microbial communities due to temperature acclimation is an important mechanism of host plasticity and adaptation in N. vectensis (Baldassarre, Ying, et al, 2021). The higher thermal tolerance of animals acclimated to high temperature could be transferred to non-acclimated animals through microbiota transplantation (Baldassarre, Ying, et al, 2021).…”
Section: Microbial Plasticity Is Promoting Animal Adaptationsmentioning
confidence: 79%
See 2 more Smart Citations